PINK OCTOBER PET EXTENSION PROJECT: THE IMPORTANCE OF RAISING AWARENESS AMONG PET OWNERS AND STUDENTS ABOUT BREAST CANCER IN VETERINARY MEDICINE - de Lira, Maria Augusta Freitas Barbosa Paiva; Sousa, Emanuella Maria Elen Moraes; da Silva, José Eduardo Vieira; Lins, Isabela de Andrade Lima Barreto; Vieira, Natália Araújo; Camargo, Karine Silva (Seven Editora, 2026)
Mammary neoplasms are among the main oncological conditions in small animal practice, presenting high prevalence in female dogs and highly malignant behavior in female cats, and are frequently diagnosed at advanced stages. This scenario is associated, among other factors, with owners’ lack of information regarding the use of progestogens, early clinical signs, and preventive measures, such as early spaying. Therefore, the present study aimed to describe and analyze the importance of a university extension project, developed within the context of the “Pink October Pet” campaign, in raising awareness among dog and cat owners and in the technical-scientific training of Veterinary Medicine students regarding mammary cancer in female dogs and cats. This is an experience report of a descriptive and qualitative nature, carried out through in-person educational activities, a digital social media campaign, and a scientific event, involving owners, students, and professionals in the field. The results demonstrated a wide reach of the extension activities, both in person and on digital platforms, in addition to high participant engagement. An improvement in owners’ knowledge regarding prevention and early diagnosis was observed, as well as a significant contribution to the practical, scientific, and humanized training of the students involved. It is concluded that university extension projects constitute effective tools for animal health education, promoting community awareness and reinforcing the social role of the university in the prevention of mammary neoplasms in small animals.